FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEKURANGAN ENERGI KRONIS ( KEK )PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS LIMBOTO - Harismayanti Harismayanti; Ani Retni; Miftahul Jannah (Universitas Muhammadiyah Gorontalo, 2019)
Chronic energy deficiency is a condition of a person suffers from an imbalance in nutrients intake (energy and protein) during pregnancy or persists. The objective of research was to obtain the factors are related with the incidents of chronic energy deficiency in pregnant women. The design used Quantitative analytic survey with cross sectional approach. Collecting sample used random sampling with 190 respondents. Analysis used chi square test with significance ɑ = 0,05, the result obtained there is relationship between economy status with CED ρ = 0,02< 0,05, there is relationship between education with CED ρ = 0,003 < 0,05, and there is relationship between parity and CED with ρ = 0,04 < 0,05. Suggestion is expected to increase in giving a socialization or clearly information to pregnant women about CED.